La criminalización de la disidencia contra el extractivismo en el Perú. La atribución de la responsabilidad penal a la acción política: Análisis a la luz del caso Aduviri - Vásquez, Mirtha (2018)
Validity of human rights in contexts of extractive activity is at the core of a debate around social conflict, currently arising in the country. Conflicts emerging from social and environmental problems created by extractivism have not been properly addressed by the State. The use of repressive mechanisms is more and more questioned, mainly since there is a wider criminalization of the exercise of basic freedoms, such as, the freedom of speech, freedom of opinion, and the right to participate in political decisions that are essential elements to democracy. A rising number of prosecutions against leaders of social movements reveals the use of punitive power to retaliate against those considered as “disruptors” of a hegemonic order being imposed. The Aduviri Case, concerning the prosecution and conviction of a leader of the Aymara movement, who conducted a resilient protest process against mining concessions in the South of the country in 2011, will serve as a reference to the analysis.